Association of Radiation Timing with Long-Term Satisfaction and Health-Related Quality of Life in Prosthetic Breast Reconstruction. Issue 1 (2nd May 2022) - Nelson, Jonas A.; Cordeiro, Peter G.; Polanco, Thais; Shamsunder, Meghana G.; Patel, Aadit; Allen, Robert J.; Matros, Evan; Disa, Joseph J.; Cuaron, John J.; Morrow, Monica; Mehrara, Babak J.; Pusic, Andrea L.; et al.
Abstract : Background: Radiation therapy is increasingly used after breast cancer surgery, which may impact patients' postoperative quality of life. This study assessed differences in long-term patient satisfaction and health-related quality of life after radiation therapy administered at different stages of implant-based breast reconstruction or with no radiation after surgery. Methods: In this observational study, long-term outcomes were evaluated for four cohorts of women who completed breast reconstruction and received (1) no radiation, (2) radiation before tissue expander placement, (3) radiation after tissue expander placement, or (4) radiation after permanent implant between 2010 and 2017 at Memorial Sloan Kettering. Satisfaction and health-related quality of life were assessed using the prospectively collected Satisfaction with Breasts and Physical Well-Being of Chest BREAST-Q subscales. Score distributions were examined by radiation exposure status for 3 years after surgery using nonparametric analyses and regression models. Results: Of 2932 patients who met the inclusion criteria, 25.8 percent received radiation during breast cancer treatment, including before tissue expander placement ( n = 239; 8.2 percent), after tissue expander placement ( n = 290; 9.9 percent), and after implant placement ( n = 228; 7.8 percent). Radiotherapy patients had average scores 7 to 9 points lower at all postoperative time points for Satisfaction with Breasts and Physical Well-Being of Chest subscales ( p < 0.001). Although patient-reported outcomes did not differ by radiation timing, there were higher rates of severe capsular contracture with postimplant radiotherapy ( p < 0.001). Conclusions: Radiation therapy significantly affected patient satisfaction and health-related quality of life following implant breast reconstruction through 3 years postoperatively. Patient perception of outcome was unaffected by radiotherapy timing; however, capsular contracture was higher after postimplant radiotherapy, suggesting there may be an advantage to performing radiotherapy before placement of the final reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.